Characterization of diffusing sub-10 nm nano-objects using single anti-resonant element optical fibers - Torsten Wieduwilt; Ronny Förster; Mona Nissen; Jens Kobelke; Markus A. Schmidt (Nature Communications, 2023)
Abstract Accurate characterization of diffusing nanoscale species is increasingly important for revealing processes at the nanoscale, with fiber-assisted nanoparticle-tracking-analysis representing a new and promising approach in this field. In this work, we uncover the potential of this approach for the characterization of very small nanoparticles (<20 nm) through experimental studies, statistical analysis and the employment of a sophisticated fiber and chip design. The central results is the characterization of diffusing nanoparticles as small as 9 nm with record-high precision, corresponding to the smallest diameter yet determined for an individual nanoparticle with nanoparticle-tracking-analysis using elastic light scattering alone. Here, the detectable scattering cross-section is limited only by the background scattering of the ultrapure water, thus reaching the fundamental limit of Nanoparticle-Tracking-Analysis in general. The obtained results outperform other realizations and allow access to previously difficult to address application fields such as understanding nanoparticle growth or control of pharmaceuticals.